Serum paraoxonase and arylesterase activities in patients with lung cancer in a Turkish population - Elkiran, Emin T.; Mar, Nefsal; Aygen, Bilge; Gursu, Ferit; Karaoglu, Aziz; Koca, Suleyman (Bmc, 2007)
Background: Lung cancer (LC) is the leading cause of cancer-related deaths. Oxidative DNA damage may contribute to the cancer risk. The antioxidant paraoxonase (PON1) is an endogenous free radical scavenger in the human body. The aim of this study was to determine serum PON1 and arylesterase ( ARE) activities in patients with newly diagnosed LC. Methods: This case control study involved a total of 39 patients with newly diagnosed LC ( untreated) and same number of age- and sex-matched healthy individuals. Serum PON1 and ARE activities in addition to lipid parameters were measured in both groups. Results: Serum PON1 and ARE activities were found to be lower in patients with LC compared to the controls ( p = 0.001 and p = 0.018, respectively). The ratio of PON1/high density lipoprotein (HDL) was significantly lower in the LC group compared to the control one ( p = 0.009). There were positive correlations between the serum levels of HDL and PON1 in both the control (r = 0.415, p = 0.009) and the LC groups ( r = 0.496, p = 0.001), respectively. PON1 enzyme activity was calculated as three different phenotypes in both groups. In regard to lipid parameters, total cholesterol levels were significantly lower ( p = 0.014) in the LC group whereas the other lipid parameters such as HDL, LDL, and triglyceride levels were not significantly different among groups. Conclusion: Serum PON1 activity is significantly low in the LC group compared with the healthy controls. Metastasis status and cigarette smoking do not affect serum PON1 activity in the LC patients.
Keywords: Low-Density-Lipoprotein; Oxidative Stress; Malondialdehyde Levels; Free-Radicals; Lipid-Peroxidation; Gene Polymorphisms; Prostate-Cancer; Oxygen Radicals; Association; Risk